THE EFFECT OF TRADE CREDIT ON COMPANY PROFITABILITY - Munawar Chalil; Sylvia Veronica Siregar (UIN Mataram, 2021)
Our study aims to analyze the effect of trade credit on company profitability and the non-linear relationship between them for the period 2010 - 2019. The study used panel data methodology to examine a sample of 254 non-financial sector companies listed on the Indonesia Stock Exchange. The study found an inverted curve-shaped relationship between trade credit receivables and profitability. However, empirical studies also found insufficient evidence to explain a non-linear relationship between trade credit payable and profitability. In addition, the study found a negative and significant effect of company size and sales fluctuation in moderating the relationship between trade credit and profitability. moderation of this variable in the non-linear relationship between trade credit receivables and profitability shifts the optimal point value for trade credit utilization to a lower level. The study concludes that the company should maintain its trade credit receivable level as close as its optimum point to maximize the profitability by considering company size, the stability of sales, and considering the classification of the company's sector that causes a shift in the optimal point of trade credit. The paper gives empirical evidence of a non-linear relationship between trade credit receivable and profitability; consequently, the company can precisely determine the optimal value in investing in trade credit receivable.